2009
DOI: 10.2503/jjshs1.78.300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Temperature on Pollen Quality, Ovule Fertilization and Development of Embryo and Achene in ‘Tochiotome’ Strawberry

Abstract: Effects of high temperature (HT) on pollen quality, ovule fertilization and development of embryo and achene were investigated in relation to fruit malformation in 'Tochiotome' strawberry (Fragaria × ananassa Duch.). When the flower bud of the first inflorescence was developing, plants were transferred to HT (32/27°C) and control temperature (CT: 27/22°C) rooms. At anthesis, anthers were collected from flowers in the first (1st) and second (2nd) inflorescences to examine pollen viability and germination. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…In this context, it has been reported that environmental factors such as high temperatures during achene development can induce early embryo abortion in strawberry fruits (Pipattanawong et al, 2009). Factors which influence achenes viability (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it has been reported that environmental factors such as high temperatures during achene development can induce early embryo abortion in strawberry fruits (Pipattanawong et al, 2009). Factors which influence achenes viability (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These differences in achenes size could be indicating a low reproductive capability (Pipattanawong et al, 2009), which in turn would translate into a loss of achene's physiological functionality. If this is true, it would probably involve a lower capacity to secrete auxins (Mudge et al, 1981;Dreher & Poovaiah, 1982) and/or the uncoupling of the metabolic synchrony between achenes and receptacle during the early stages of fruit development (Fait et al, 2008 and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been performed on the high-temperature effects on fruit development and fruit quality 19 , and it is obvious that high temperatures inhibit fruit growth and development and impair quality. Many technological approaches for coping with high temperatures within a greenhouse or high tunnels have been developed, several of which were presented at the 2007 spring JSHS symposium 27 .…”
Section: Improvement Of Cultural Conditions Especially High-temperatmentioning
confidence: 99%
“…The mechanism is based on the amount of fertilized achenes [17], the true 'nut'-fruits of strawberry being an aggregated fruit [18]. Unfertilized achenes are a result of pollination limitation [28] and have no physiological functionality [29]. Aggregations of unfertilized achenes usually lead to deformations in strawberry fruits [17,30] and thus deformations can be directly linked to insufficient pollination.…”
Section: Pollination Limitation and Fruit Deformationmentioning
confidence: 99%